Effective behaviour management in the primary classroom - Shelton, Fiona (McGraw Hill/Open University Press, 2008)
Successful teaching requires a thorough understanding of a range of effective behaviour management strategies. Through the use of case studies, reflective tasks, and experiences and examples from the classroom, this book aims to generate an accessible approach to the hows and whys of behaviour management.